Bilateral Cochlear Implants and Bimodal Hearing: A Comparison of Quality of Life - Lewis, Jessica H.; Castellanos, Irina; Tamati, Terrin N.; Moberly, Aaron C. (Journal of the American Academy of Audiology, 2024)
Background Despite significant advances in the field of cochlear implants (CIs), there is no widely accepted criterion for when to counsel on bilateral CIs in adults. This is partly due to conflicting findings on the advantages of bilateral CIs versus bimodal hearing (i.e., CI with a contralateral hearing aid). Because of this, clinicians rely on a poorly defined combination of clinical measures and patient discussion to evaluate a patient's listening needs and preferences. Patients' needs and preferences are often used to guide recommendations on whether bilateral CIs or bimodal hearing is best for that individual, suggesting that an in-depth comparison of each group's self-reported outcomes is warranted.Purpose Given the limited number of studies directly comparing quality of life (QoL) in bimodal and bilateral patients, the current study conducted a preliminary comparison of self-reported outcomes to better understand patient-reported benefits of each listening configuration.Research Design This was a between-subjects comparison.Study Sample Fifteen bimodal and nine bilateral adult CI users made the study sample.Data Collection and Analysis Participants completed the Cochlear Implant Quality of Life (CIQOL) Profile 35. For group comparison purposes, monosyllabic word recognition and nonverbal intelligence were measured. Independent samples t-tests with Holm–Bonferroni corrections were used to compare bimodal and bilateral patients across domains of the CIQOL.Results Bilateral CI users self-reported better environmental, emotional, social, and global QoL when compared to bimodal users. The groups did not differ on age, nonverbal intelligence, speech recognition abilities, and duration of hearing loss; however, bimodal users had less experience listening with their CI than the bilateral CI users.Conclusion Bilateral CI users showed widespread advantages in QoL when compared to bimodal users. Bilateral CI users self-reported significantly better environmental QoL which conflicts with previous in-lab and self-report results suggesting a bimodal advantage. Additionally, due to a lack of current literature, it is unclear why a bilateral advantage is observed for emotional and social QoL. Results of the current study not only provide additional support on the benefits of bilateral implantation but also stress the need to further explore the self-reported benefits of each listening configuration.
Keywords: bimodal benefit; cochlear implants; quality of life; patient-reported outcome measures